Battery energy storage system size determination in renewable energy systems: A review. (August 2018) - Yang, Yuqing; Bremner, Stephen; Menictas, Chris; Kay, Merlinde
Abstract: Renewable energy, such as hydro power, photovoltaics and wind turbines, has become the most widely applied solutions for addressing issues associated with oil depletion, increasing energy demand and anthropogenic global warming. Solar and wind energy are strongly dependent on weather resources with intermittent and fluctuating features. To filter these variabilities, battery energy storage systems have been broadly accepted as one of the potential solutions, with advantages such as fast response capability, sustained power delivery, and geographical independence. During the implementation of battery energy storage systems, one of the most crucial issues is to optimally determine the size of the battery for balancing the trade-off between the technical improvements brought by the battery and the additional overall cost. Numerous studies have been performed to optimise battery sizing for different renewable energy systems using a range of criteria and methods. This paper provides a comprehensive review of battery sizing criteria, methods and its applications in various renewable energy systems. The applications for storage systems have been categorised based on the specific renewable energy system that the battery storage will be a part. This is in contrast to previous studies where the battery sizing approaches were either arranged as an optimised component in renewable systems or only accounted for one category of renewable system. By taking this approach, it becomes clear that the critical metrics for battery sizing, and by extension the most suitable method for determining battery size, are determined by the type of renewable energy system application, as well as its size. This has important implications for the design process as the renewable energy system application will drive the battery energy storage system sizing methodology chosen.